PERAN GAPOKTAN DALAM MENINGKATKAN KESEJAHTERAAN KELOMPOK TANI PADI DI DESA SALATIGA KECAMATAN MANDOR KABUPATEN LANDAK - Herpranoto Firdo; Kusnadi, iwan; Iva Ashari, Ananda (Lunggi Journal, 2024)
This study aims to determine the Farmer Group programs in improving farmer welfare, to find out the steps taken by Farmer Group in improving, to find out the results of Farmer Group activities in improving farmer welfare. This study uses qualitative methods and a descriptive approach. The study was conducted in Salatiga Village Mandor District Landak Regency. From July to August 2024. The subjects of this study were Farmer Groups in Salatiga Village. The informants in this study were the Head of Farmer Group, Agricultural Center, Head of Farmer Group, Secretary of Farmer Group, and Members of Farmer Group. Data collection was carried out using interview, observation, and documentation methods. Data validity checks were carried out by extending participation, diligent observation and examination by research data sources. Technical data analysis was carried out using an inductive model consisting of data collection, data reduction, data presentation, and drawing conclusions. The results of this study indicate that: (1) the role of the farmer group carried out in Salatiga Village, which plays a role in facilitating, fostering, directing farmers so that they can prosper in farming rice, then Farmer Group holds extension programs, development of modern agricultural technology, farming training, regular meetings in multipurpose buildings and comparative studies to other areas. (2) There are still inhibiting factors for farmers in Salatiga Village such as many pests, slashing rats, sparrows, caterpillars, snails, equivalent to weather factors